2016
DOI: 10.17816/jowd6546-14
|View full text |Cite
|
Sign up to set email alerts
|

Woman’s microbiota and pregnancy outcomes

Abstract: A local inflammatoMicrobial invasion of amniotic cavity and subsequent infection process are the leading cause of adverse pregnancy outcomes. Intra-amniotic infection can be caused by both pathogenic and opportunistic microorga­nisms and viruses, but in the vast majority of cases intra-amniotic infection is associated with the normal microflora of different body sites – the vagina, intestines, mouth and respiratory tract. In the paper, current views about the role of infection factor in the adverse pregnancy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…Микробиоценоз влагалища находится в равновесии, пока естественная резистентность и иммунная система обеспечивают барьерную функцию [1,2]. Любая дисфункция микрофлоры влагалища во время беременности повышает восприимчивость к различным инфекциям, передаваемым половым путем (ИППП) [3][4][5][6], а инфекции в 40% наблюдений становятся причиной преждевременных родов и других осложнений гестации [6][7][8][9].…”
Section: Introductionunclassified
“…Микробиоценоз влагалища находится в равновесии, пока естественная резистентность и иммунная система обеспечивают барьерную функцию [1,2]. Любая дисфункция микрофлоры влагалища во время беременности повышает восприимчивость к различным инфекциям, передаваемым половым путем (ИППП) [3][4][5][6], а инфекции в 40% наблюдений становятся причиной преждевременных родов и других осложнений гестации [6][7][8][9].…”
Section: Introductionunclassified
“…Various authors report that 25-50% of women with infertility are diagnosed with endometriosis and the peritoneal form of endometriosis is accompanied by infertility in 60-80% of cases [6][7][8][9][10]. The meta-analysis by Barnhart [11] revealed that pregnancy rates in women with endometriosis were one half as high as in those of women with tubal pregnancy.…”
Section: Introductionmentioning
confidence: 99%